Pan-cancer analysis of LINC02535 as a potential biomarker and its oncogenic role in lung adenocarcinoma - Shuang Dai; Tao Liu; Ying-Ying He; Yan Huang; Li Wang; Feng Luo; Yan Li (Heliyon, 2022)
Background: LINC02535 has gained much attention for its oncogenicity across several cancers, but the systematic pan-cancer analysis of LINC02535 has not been carried out before. Methods: Herein, we explored the expression level, prognostic value, and hallmark pathways of LINC02535 across multiple cancers using the Cancer Genome Atlas (TCGA) and Cancer Cell Line Encyclopedia (CCLE) databases. Moreover, the expression and biological features of LINC02535 in lung adenocarcinoma (LUAD) were confirmed by qRT-PCR, in vitro and in vivo experiments. Results: LINC02535 is differentially expressed in 10 of 17 human cancers and serves as a favorable or unfavorable biomarker in distinct cancer types. Gene set enrichment analysis (GSEA) indicated that key oncogenic pathways/phenotypes were remarkably activated in most cancers with intratumoral increased LINC02535, whereas these pathways/phenotypes were suppressed in other cancer types (colon adenocarcinoma, kidney renal clear cell carcinoma, rectal adenocarcinoma) with intratumoral decreased LINC02535. Of note, the epithelial-mesenchymal transition (EMT) phenotype was greatly enriched in LUAD patients with elevated LINC02535. Based on the TCGA and CCLE datasets, LINC02535 was positively correlated with the EMT-related gene CD73 (also named as NT5E, an immunosuppressive gene) in almost all cancer types (Spearman R > 0.5, P < 0.001) including LUAD. Most importantly, qRT-PCR confirmed that LINC02535 was upregulated in lung cancer cells or tissues as opposed to human bronchial epithelial cells or paratumor tissues. Knockdown of LINC02535 inhibited proliferation, migration of LUAD cells and retarded xenografted tumor growth. Moreover, silencing of LINC02535 induced apoptosis and cell cycle arrest at G1 phase. Conclusions: The findings from our pan-cancer analysis provide a relatively comprehensive understanding of the potential value of LINC02535 across multiple cancers, and the oncogenic role of LINC02535 in LUAD has been confirmed.